Desenvolvimento de aparato ditático-experimental de canal de distribuição de água - Alves, Fabrício Leite (Universidade Federal Rural do Semi-Árido, 2019)
The study of hydraulic supply services has been instrumental in understanding the needs of the world's population in terms of services, infrastructure, water supply facilities, urban storm drains and other activities. Therefore, various policies are invested in the water supply system using equipment and services to treat and subsequently distribute drinking water for domestic, industrial and other public services. Currently, water treatment plants are designed through new technologies that increasingly improve the projects developed. For this, software simulations are carried out, contributing to the improvement of the existing real situations. Besides that, these simulations can aid in the teaching-learning of engineering students. The main purpose of this paper is the construction of a small scale experimental apparatus for the water distribution line water from an existing software with procedure in Visual Basic for Applications, based on the requirements of NBR 12.216 (ABNT, 1992). To validate the device built, carried out through two steps: calibration of the system water flow and use of the volumetric method and E. R. Yassuda, P. Nogami, R. Montrigaud for flow measurement. With the obtained results it was possible to perceive that the work was favorable in the acquisition of knowledge of the engineering students, in order to improve their discernment about the water distribution system and to simulate a real situation within the educational scope.
Monografia
Keywords: Hidráulica; Aparato experimental; Distribuição de água; Simulações hidráulicas; Abastecimento de água; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA